Efficacy of gemcitabine plus erlotinib in rash-positive patients with metastatic pancreatic cancer selected according to eligibility for FOLFIRINOX: A prospective phase II study of the 'Arbeitsgemeinschaft Internistische Onkologie'. (May 2018) - Haas, M.; Siveke, J.T.; Schenk, M.; Lerch, M.M.; Caca, K.; Freiberg-Richter, J.; Fischer von Weikersthal, L.; Kullmann, F.; Reinacher-Schick, A.; Fuchs, M.; Kanzler, S.; Kunzmann, V.; et al.
Abstract: Introduction: In metastatic pancreatic ductal adenocarcinoma (mPDAC) treatment, erlotinib is known to be more effective in patients developing skin rash. Treatment with the FOLFIRINOX regimen is only performed in fit patients following defined inclusion criteria. The present study investigates the efficacy of gemcitabine plus erlotinib (gem/erlotinib) in rash-positive patients fit for FOLFIRINOX. Patients and methods: For this prospective phase II study, 150 patients were recruited in 20 centres. All patients received gem/erlotinib for 4 weeks (run-in phase); the subsequent treatment was determined by the development of skin rash: patients with rash grades 1–4 continued with gem/erlotinib, rash-negative patients were switched to FOLFIRINOX. Primary study end-point was to achieve a 1-year survival rate in rash-positive patients ≥40%. Results: Ninety patients were deemed positive for skin rash by the end of the run-in phase, showing a 1-year survival rate of 40.0% (95% confidence interval [CI] 29.8–50.9). Median overall survival (OS) was 10.1 months, progression-free survival (PFS) was 3.8 months and overall response rate (ORR) was 23.3%. Patients switched to FOLFIRINOX ( n = 27) had a 1-year survival rate of 48.1% (95% CI 28.7–68.1), a median OS of 10.9 months, a median PFS of 6.6 months and an ORR of 33.3%. Rash-negative patients had a lower quality of life at baseline but seemed to experience an improved control of pain during FOLFIRINOX. Conclusions: First-line treatment with gem/erlotinib was effective in fit, rash-positive mPDAC patients achieving a 1-year survival rate comparable to previous reports for FOLFIRINOX. The study was registered at clinicaltrials.gov (NCT0172948) and Eudra-CT (2011-005471-17). Highlights: Selected patients with skin rash by erlotinib had a 1-year survival rate of 40%. In rash-negative patients, FOLFIRINOX was an effective salvage treatment. FOLFIRINOX seemed to preserve and improve patients' quality of life.